A virtual species set for robust and reproducible Species Distribution Modelling tests - Garzon-Lopez, Carol X; Rocchini, Duccio; Bastin, Lucy; Foody, Giles M (Supplement to: Garzon-Lopez, CX et al. (2016): A virtual species set for Species Distribution Modelling robust and reproducible test. Data in Brief, 7, 476-479, https://doi.org/10.1016/j.dib.2016.02.058, 2015)
Predicting species potential and future distribution has become a relevant tool in biodiversity monitoring and conservation. In this data article we present the suitability map of a virtual species generated based on two bioclimatic variables, and a dataset containing more than 700.000 random observations at the extent of Europe. The dataset includes spatial attributes such as, distance to roads, protected areas, country codes, and the habitat suitability of two spatially clustered species (grassland and forest species) and a wide spread species.